New modulation scheme for bidirectional quasi z-source modular multilevel converters - Khera, Fatma; Klumpner, Christian; Wheeler, Patrick (2018)
This paper proposes a dedicated modulation scheme for a bidirectional quasi Z-source modular multilevel converter (BqZS-MMC). The operation principle and a suitable PWM method are proposed. The relation between the modulation index and shoot-through duty ratio is derived. A formula for calculating the required value of quasi Z-source capacitance is given. The simulation results presented in the paper validate the operation and the performance of the proposed topology.